You say, "cariño"; I say, "caring": Latino newcomer immigrant families in the middle. Issue 5 (19th October 2016) - Rodríguez-Castro, Mónica; Salas, Spencer; Murray, Beth
Abstract: One of the 16 core beliefs of middle level thinking is that schools and families must work together on behalf of every young adolescent (National Middle School Association, 2010). However, in classrooms and on curriculum nights, communication emerges as a critical issue. This is especially true when it comes to teachers' interacting with Latino immigrant newcomer families. That is to say, in our regional context, the vast majority of middle level educators and administrators are monolingual English speakers; they themselves often see their monolingualism/culturalism as a stumbling block for communicating caring to Latino parents and the trust such caring generates. A recurring question we encounter in our various teacher education courses and on-site with our partners is: "How can teachers and institutions demonstrate a language and practice of caring in situations when they do not necessarily speak the same language?" Drawing from intercultural communication theory, we outline two over-arching intercultural communication principles that can be leveraged for communicating our interconnectedness and interdependence within and beyond increasingly culturally and linguistically diverse schooling contexts. Our intent here is more than to argue that we should care. Rather, we hope to provide practitioners with concrete intercultural "moves" for initiating the safe, productive learning spaces where Latino newcomer families can engage in the collaborative work of schools